Determination of Mineral Processing Induced Environmental Impacts - Kursun, Ilgin (Asian Journal of Chemistry, 2010)
In this study, the mineral processing, envirotimentaI technology and the application of new or improved methods both of mineral processing and the treatment of solid and liquid wastes is discussed, and to provide the appropriate background to apply mineraI processing techniques so as to minimize environmental degradation.